Influence of operating speed, load and mileage on the lubricating performance of self-lubricating rolling linear guide. - Haiyong Wu; Na Lin; Bihua Shen; Li Liu; Erjun Lu; Guosheng Xu; Qiqin Cai; Yang Chen; Xiaohui Chen (PLoS ONE)
Self-lubricating rolling linear guides are widely used in precision instruments, industrial automation production lines, and other fields. The lubrication performance of rolling linear guide has a significant impact on their smooth operation and service life. This paper aims to investigate influence of different operation condition on the lubricating performance of rolling linear guide. Polytetrafluoroethylene (PTFE) is employed as the substrate to fabricate porous media which is installed at the end cover of the rolling linear guide slider to study the effects of operating speed, load, and mileage on the oil film thickness of rolling linear guide. The thickness of lubricating oil film is basically linearly proportional to the operating speed. The influence of load and operating mileage on the thickness of lubricating oil film is not significant. The oil storage rate gradually decreases with the operating mileage increases. The internal pores of porous media have good connectivity. The interconnection of various pores is beneficial for oil storage, oil control, and oil leakage during the operation of rolling linear guides. The self-lubricating rolling linear guide is in a fully film elastohydrodynamic lubrication state which can achieve good lubrication for the rolling linear guide. The results of the studies could provide theoretical reference for improving the self-lubricating performance of rolling linear guides.